Analysis of the Impact of Digital Transformation on Economic Productivity in the Manufacturing Industry Sector in Tangerang Regency - Jhonny Zainal Abidin; Bambang Bernanthos (Journal Markcount Finance, 2024)
This study analyzes the impact of digital transformation on economic productivity in the manufacturing industry sector in Tangerang Regency, involving 100 respondents from various sectors, including food and beverages, textiles, chemicals, as well as automotive and electronics. The questionnaire explores demographic aspects such as position, industry sector, and scale of the company. The results of the demographic analysis indicate that most respondents are operational and production managers, with 50% coming from medium-scale companies. Validity and reliability tests show that all questionnaire items are valid (p < 0.05) and that the Cronbach's Alpha coefficient is 0.76, indicating good consistency. Linear regression analysis reveals a significant positive relationship between the adoption of digital technology and productivity, with a regression coefficient of 0.65 (p < 0.01), meaning an increase of one unit in the adoption of digital technology is associated with a productivity increase of 65%. With an R-squared value of 0.72, these findings indicate that 72% of the variation in economic productivity can be explained by the adoption of digital technology. This research provides important insights into how the implementation of digital technology can enhance productivity in the manufacturing sector and recommends the importance of effective digital transformation strategies to improve competitiveness and performance in the era of Industry 4.0.